Calibration of a system for on-line monitoring of electron energy and absorbed dose at an industrial accelerator LU-10 - Pomatsalyuk, R.I.; Tytov, V.Yu.; Titov, D.V.; Uvarov, V.L.; Shevchenko, V.A. (Вопросы атомной науки и техники, 2020)
Particle beam energy and absorbed dose are critical parameters of product processing at industrial electron accelerators. For on-line monitoring of those parameters, a method based on measuring of distribution of the charge induced by irradiation in a wide-aperture stack-monitor, positioned behind an irradiated object, has been developed. A brief review of a control system for monitoring of the processing parameters created with the use of the EPICS package as well as the data of its operating experience at an LU-10 Linac of NSC KIPT are presented in the article. The procedure and results of calibration of the measuring channels within the electron energy range 8…10 MeV are described.